Zingiber Macradenium K. Schum, an Endemic Ginger From Sumatera: Traditional use and Antimicrobe Potential - Linda Agustin; Nurainas Nurainas; Syamsuardi Syamsuardi; Chairul Chairul (Green Publisher Indonesia, 2021)
The Zingiber genus has 84 species and varieties in the Malesia region, one of which is Zingiber macradenium K. Schum. This species is endemic to Sumatra. Zingiber macradenium K. Schum with the local name Lampuriang has been used as a toothache medicine by local people in several locations in West Sumatra. This study conducted in-depth interviews with 8 (eight) key informants who were guided by a questionnaire and the data were analyzed qualitatively and quantitatively using the ICS (Index of Cultural Significance) and UV (Use Value) formulas, antibacterial test using the paper disc diffusion method. The results of the study show that the rhizome of Z. macradenium is used in addition to treating itching, lumbago and other uses by means of research. Antibacterial test showed potential as an antibacterial with a strong inhibitory diameter.